HEALTH DISORDERS, INCLUDING PHYSICAL DEVELOPMENT AMONG YOUNG PEOPLE IN THE CONTEXT OF THE COVID-19 PANDEMIC - Nazarov Firuz Yusufovich, Yarmukhamedova Saodat Khabibovna (Journals Park Publishing, 2022)
It is known that persons of adolescent and adolescent age are vulnerable from the standpoint of health-saving due to both pronounced eco-sensitivity, physical and mental instability, and the difficulties of adaptation to sudden changes in living conditions that are inherent in a young growing organism, despite the physiological slowdown in the processes of morpho-functional development in late puberty. At the same time, the issues of correlation of biologically regular reference standards of physical parameters of development as indicators of health status are of particular importance in scientific research. The value of studies of morpho-functional features increases in relation not only to social, economic, environmental factors, but also risk factors that have arisen as a result of the spread of COVID-19.
Keywords: COVID-19, youth, medical and social support